Re-evaluation of the 13C isotope fractionation associated with lipids biosynthesis by position-specific isotope analysis of plant fatty acids. (December 2022) - Julien, Maxime; Zhao, Yu; Ma, Ran; Zhou, Youping; Nakagawa, Mayuko; Yamada, Keita; Yoshida, Naohiro; Remaud, Gérald S.; Gilbert, Alexis
Highlights: Fatty acids from C3 plants present a non-stochastic 13 C intramolecular distribution. This pattern is inherited from sugar and isotopic fractionation during biosynthesis. Acetyl-CoA carboxylase-catalyzed reaction is associated with a 13 C isotope effect. Fatty acids 13 C pattern could be preserved in n -alkanes through diagenesis. Abstract: Carbon-13 position-specific isotope analysis of fatty acids from vegetable oils was performed using Nuclear Magnetic Resonance in the present study. The measured 13 C patterns are not totally in accordance with the conventional view of the relative 13 C-depletion of acetogenic lipids and their alternation of 13 C-enriched and 13 C-depleted carbon positions. The results presented here provide a new evaluation of the isotopic fractionation associated with fatty acids biosynthesis. Whereas it is commonly acknowledged that the pyruvate dehydrogenase (PDH) is responsible for the 13 C distribution within fatty acids, data from the present work demonstrate that the conversion of acetyl-CoA to malonyl-CoA catalyzed by acetyl-CoA carboxylase (ACC) needs to be considered while explaining the measured non-stochastic 13 C pattern within fatty acids. These data combined with steady-state calculations give a new description of metabolic steps responsible for the typical 13 C intramolecular distribution of acetogenic lipids. In addition, the non-stochastic pattern measured in these plant fatty acids is similar to those previously detected within long-chain n -alkanes suggesting a preservation through geological time and demonstrating the interest of position-specific isotope analysis for studying the evolution of metabolic pathways.